(untitled) (Revista Argentina de Musicología, 2022)
The documentation of women’s musical activities in the music industry during the 1920s shows their prolific participation in the Buenos Aires’ emerging musical scene. Based on this documentation, I affirm that women tango musicians of the 1920s contributed with a unique mode of musicking to the social and cultural construction of tango as national music. In this article I will analyze the concepts of identity, nation and gender in Argentine popular music at the beginning of the record industry. Basing my work in the ideas brought by the experientalist perspective on nation, combined with recent studies that deal with the socio-cultural aspects of tango in terms of gender and sexuality, I propose to contribute to this underresarched topic through the negotiation representativity process that tango has undergone as an expression of national music.